a(1+2a)-a(4a-5)=

Simple and best practice solution for a(1+2a)-a(4a-5)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for a(1+2a)-a(4a-5)= equation:


Simplifying
a(1 + 2a) + -1a(4a + -5) = 0
(1 * a + 2a * a) + -1a(4a + -5) = 0
(1a + 2a2) + -1a(4a + -5) = 0

Reorder the terms:
1a + 2a2 + -1a(-5 + 4a) = 0
1a + 2a2 + (-5 * -1a + 4a * -1a) = 0
1a + 2a2 + (5a + -4a2) = 0

Reorder the terms:
1a + 5a + 2a2 + -4a2 = 0

Combine like terms: 1a + 5a = 6a
6a + 2a2 + -4a2 = 0

Combine like terms: 2a2 + -4a2 = -2a2
6a + -2a2 = 0

Solving
6a + -2a2 = 0

Solving for variable 'a'.

Factor out the Greatest Common Factor (GCF), '2a'.
2a(3 + -1a) = 0

Ignore the factor 2.

Subproblem 1

Set the factor 'a' equal to zero and attempt to solve: Simplifying a = 0 Solving a = 0 Move all terms containing a to the left, all other terms to the right. Simplifying a = 0

Subproblem 2

Set the factor '(3 + -1a)' equal to zero and attempt to solve: Simplifying 3 + -1a = 0 Solving 3 + -1a = 0 Move all terms containing a to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + -1a = 0 + -3 Combine like terms: 3 + -3 = 0 0 + -1a = 0 + -3 -1a = 0 + -3 Combine like terms: 0 + -3 = -3 -1a = -3 Divide each side by '-1'. a = 3 Simplifying a = 3

Solution

a = {0, 3}

See similar equations:

| 25x^4=61x^2-36 | | 12(h-1)=6h+4+2 | | -2m+0=180(-49y) | | 198=x+2*x*2 | | 14+5(2x+2)=-5 | | 8+3x+4=10 | | 198=x+2+x+2 | | 7-2n-n=-14 | | 12/42=4w/56 | | -2+0=180(-49y) | | w=3ab | | x/8.9=22 | | 2z+8=4z-4 | | 4(2x-5)=-2(7-3x) | | -150h=400 | | 4x-1=2x-1+x+2 | | 198=l*w*h | | 4x-50=3x+50 | | 0=-16t^2+30t+5 | | 5x-22+8x+46=180 | | t+9-8=5 | | 7x-6=6x-15 | | -5(-12+3x)=-45 | | 36+x^2=-12 | | 40-3b=-b+6(3-4b) | | -2x^2-x-1=0 | | 3x^2-45+108=0 | | 2(3b-2)=3b+5 | | -s^2+4s-6=0 | | 11-4a=4 | | 8y+9=10+8y | | 14+3n=8n-3n-12 |

Equations solver categories